Asuransi Peliharaan ditinjau dari Syarat Sah Perjanjian - Kurniawidyarini, Berliana Nabilah; Rahmawati, Esti (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In Indonesia, pet insurance is still not clearly regulated. Therefore, its implementation refers to general insurance regulations. This study aims to review pet insurance based on civil law principles, particularly Article 1320 of KUHPerdata regarding the validity requirements of an agreement and Articles 246-276 of the KUHD regarding insurance law provisions. This study employs a normative juridical method with a problem approach conducted through an examination of legal and systematic principles based on applicable laws and regulations. The absence of specific regulations on pet insurance may hinder the development of the pet insurance industry, leading to the neglect of pet welfare. Furthermore, the lack of specific regulations results in insufficient guidance for providing legal protection in pet insurance and creates legal uncertainty. This study highlights the importance of legal protection for both parties and the need for specific regulations regarding pet insurance in Indonesia. This aims to enhance public trust in insurance products, provide optimal protection for pets, and support the sustainable growth of the insurance industry.